2016
DOI: 10.3109/02770903.2015.1116085
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae, and mycoplasma pneumoniae: Are they related to severe asthma in childhood?

Abstract: M. pneumoniae and C. pneumoniae may play a role in the development of severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…18 I n a p r o s p e c t i v e , c a s e -c o n t r o l s t u d y performed on 82 patients, Iramain et al showed a positive relationship between MP infection and exacerbation severity, and concluded that MP infection played an important role in the development of severe acute asthma. 19 Likewise, in the prospective assessment of 58 patients with acute exacerbation, they found that specific IgM levels were much higher in patients with severe exacerbations both for MP and Chlamydophila pneumoniae. 20 Studies associating the presence of MP in acute exacerbations with the risk of hospitalization were also contradictory.…”
Section: Discussionmentioning
confidence: 97%
“…18 I n a p r o s p e c t i v e , c a s e -c o n t r o l s t u d y performed on 82 patients, Iramain et al showed a positive relationship between MP infection and exacerbation severity, and concluded that MP infection played an important role in the development of severe acute asthma. 19 Likewise, in the prospective assessment of 58 patients with acute exacerbation, they found that specific IgM levels were much higher in patients with severe exacerbations both for MP and Chlamydophila pneumoniae. 20 Studies associating the presence of MP in acute exacerbations with the risk of hospitalization were also contradictory.…”
Section: Discussionmentioning
confidence: 97%
“…In humans, infection with M. pneumoniae can favour the development of asthma in predisposed patients and specific treatment with clarithromycin improves pulmonary function (Martin et al, 2001;Kraft et al, 2002;Hansbro et al, 2004;El Sayed Zaki et al, 2009;Atkinson, 2013;Ye et al, 2014). The proportion of asthmatics who have both IgM and IgG for M. pneumoniae increases with clinical severity (Iramain et al, 2016;Yin et al, 2017). In a mouse model, single exposure to a specific toxin of M. pneumoniae was shown to be sufficient to cause asthma-like disease with histological evidence of pulmonary eosinophilic inflammation (Medina et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…18 En un estudio prospectivo caso-control sobre 82 pacientes, Iramain y col. demostraron la asociación positiva entre la infección por MP y la gravedad de la exacerbación, y concluyeron que la infección por MP tenía un papel importante en el desarrollo del asma aguda grave. 19 D e l a m i s m a f o r m a , e n l a e v a l u a c i ó n prospectiva de 58 pacientes con exacerbación aguda, encontraron, de forma significativa, que los niveles de IgM específica fueron mucho más elevados en los pacientes con exacerbaciones graves tanto para MP como para Chlamydophila pneumoniae. 20 Los estudios que han relacionado la presencia de MP en las exacerbaciones agudas con el riesgo de hospitalización también son contradictorios.…”
Section: Discussionunclassified